Emerging drugs for immune thrombocytopenia (ITP). (2nd January 2017) - Salama, Abdulgabar
ABSTRACT: Introduction : Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by autoantibody production against platelets, increased platelet destruction, and, in some cases, impaired thrombopoiesis. The majority of affected patients have significant bleeding risks due to low platelet counts and require treatment. The etiology of ITP is an immunological labyrinth. Currently available treatment options are usually not only nonspecific, but are also associated with some risks. Areas covered : Several useful drugs for the treatment of ITP are currently available. Furthermore, ongoing trials with new drugs and preclinical development of additional drugs may help to improve and determine their value. Expert opinion : ITP is a heterogeneous complex requiring individualized treatment. None of the available drugs are specific, nor are they invariably safe and effective. Thus, the need for specific therapy is evident.